Electromyography & Portable Computing Devices: What Forearm Muscles Should be Measured?. (September 2013) - Werth, Abigail J.; Babski-Reeves, Kari
Portable computing devices have become more lightweight and mobile due to changes in the hardware of the devices. In many cases, hardware keyboards are being replacing virtual keyboards, raising concerns on changing ergonomic exposures as, for example, muscle activation patterns may vary with virtual keyboard use. The objective was to identify active forearm muscles across select computing devices. Twenty participants completed a single test session in which seven forearm muscles were evaluated using surface EMG whilst they typed on two portable computing devices (netbook and slate computer) for 5 minutes apiece. Mean normalized EMG was analyzed and indicated that slate computers resulted in significantly lower muscle activation levels than netbooks. The extensor carpi radialis, extensor carpi ulnaris, extensor digitorum communis had the highest muscle activation levels for both the slate and netbook computers. This indicates that the same muscles should be studied for both slate and netbook computers.